1988
DOI: 10.1123/ijsb.4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pedaling Rate in Cycling Using a Muscle Stress-Based Objective Function

Abstract: Relying on a five-bar linkage model of the lower limb/bicycle system, intersegmental forces and moments are computed over a full crank cycle. Experimental data enabling the solution of intersegmental loads consist of measured crank arm and pedal angles together with the driving pedal force components. Intersegmental loads are computed as a function of pedaling rate while holding the average power over a crank cycle constant. Using an algorithm that avoids redundant equations, stresses are computed in 12 lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Other reports of metabolic optimal cadence do not cover as wide a range of cadence or power (11,17,28,29). Although there is considerable discrepancy in the literature with respect to preferred cadence (14,19,21), there is general agreement that cyclists use a relatively high cadence (11,19,21) and cyclists are more efficient at higher cadences (11,29). It is also noteworthy that the world 1-h cycling record has been consistently set with average cadence just over 100 rpm (27).…”
Section: Discussionmentioning
confidence: 98%
“…Other reports of metabolic optimal cadence do not cover as wide a range of cadence or power (11,17,28,29). Although there is considerable discrepancy in the literature with respect to preferred cadence (14,19,21), there is general agreement that cyclists use a relatively high cadence (11,19,21) and cyclists are more efficient at higher cadences (11,29). It is also noteworthy that the world 1-h cycling record has been consistently set with average cadence just over 100 rpm (27).…”
Section: Discussionmentioning
confidence: 98%
“…And, according to this study, the corresponding cycling velocity regions at a cycling cadence of 40 rpm are similar to those according to the speedup mode of the commercial system. Based on the prior studies, a cyclist cycling with a cadence of 50-65 rpm consumes the least oxygen (Seabury et al, 1977;Coast and Welch, 1985) and generates minimum individual muscle iEMG, neuromuscular activation, force, stress and endurance at a cycling cadence of 90-100 rpm (Hull et al, 1988;Neptune et al, 1997;Neptune and Hull, 1999). The designed comfortable cycling cadence at 40-45 rpm is much lower than those proposed in the prior studies.…”
Section: Article In Pressmentioning
confidence: 91%
“…On the other hand, other studies are based on simulation. An optimization of cycling cadence, using a muscle stress-based cost function, revealed that the optimum cycling cadence is between 95 and 100 rpm (Hull et al, 1988). An optimized simulation based on a human endurance cycling model, carried out in a fixed output power of 265 W, showed that the minimum neuromuscular activation, force, stress and endurance occur at a cycling cadence of 90 rpm (Neptune and Hull, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…The optimum cycling cadence, based on a muscle stressbased cost function, has been found to be between 95-100 rpm (Neptune et al, 1997). It has also been found that the minimum neuromuscular activation, force, stress and endurance occurs at a cadence of 90 rpm (Hull et al, 1988).…”
Section: Biomechanics Of Cycling and Rider Comfortmentioning
confidence: 96%
“…Previous studies have shown that typical steady-state cycling over level ground at ~9 m/s the power required is ~200 W at a cadence of 65 rpm (Hull et al, 1988). More recent studies have shown that world class cyclists generate 7.6 W/kg while an average cyclist would generate 3.7 W/kg (Coggan, 2008).…”
Section: Biomechanics Of Cycling and Rider Comfortmentioning
confidence: 99%